Scientific program of DERICA—prospective accelerator and storage ring facility for radioactive ion beam research. (October 2019) - Grigorenko, L V; Sharkov, B Yu; Fomichev, A S; Barabanov, A L; Barth, W; Bezbakh, A A; Bogomolov, S L; Golovkov, M S; Gorshkov, A V; Dmitriev, S N; Eremin, V K; Ershov, S N; et al.
Abstract: Studies of radioactive ions (RIs) are the most thriving field of low-energy nuclear physics. In this paper, the concept and the scientific agenda of the prospective accelerator and storage ring facility for RI beam (RIB) research are proposed for a large-scale international project based at the Flerov Laboratory of Nuclear Reactions of the Joint Institute for Nuclear Research. The motivation for the new facility is discussed and its characteristics are briefly presented and shown to be comparable to those of advanced world centers, the so-called "RIB factories". In the project, the emphasis is made on studies with short-lived RIBs in storage rings. A unique feature of the project is the possibility of studying electron–RI interactions in a collider experiment to determine the fundamental properties of nuclear matter, in particular, electromagnetic form factors of exotic nuclei.